Identification and characterisation of a drought-responsive galactinol synthase in wild rocket (Diplotaxis tenuifolia) - Xonti, Alukhanyo (Stellenbosch : Stellenbosch University, 2023)
Thesis (MScAgric)--Stellenbosch University, 2023.